A MODEL FOR DETERMINING OPTIMAL BATCH SIZES OF MULTI-FEATURED PRODUCTS WITH RANDOM PROCESSING ACCURACIES UNDER QUALITY AND COST CONSTRAINTS - Shin, Dongmin; Kim, Jeongyeon; Cho, Geunho; Hur, Sun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Determining an optimal batch sizes in a production system that produces defective items has been the primary focus of manufacturing sector. Depending on the proportion of defectives, the amount of optimal batch size also varies depending on several cost factors such as setup cost, order cost, and defective cost. In this paper, models for the optimum batch sizes in a multi-featured products production system have been developed for quality and cost constraints. In determining the optimal batch size of products, we consider two factors the one is tool capability and another is set-up accuracy based on feature. The mathematical structure of this model has been proposed and results are demonstrated through Illustrative examples. And we compared the optimal batch sizes accordance with change in cost ratio.